Analysis of Treg cell population in patients with breast cancer with respect to progesterone receptor status - Dziobek, Konrad; Biedka, Marta; Nowikiewicz, Tomasz; Szymankiewicz, Maria; Łukaszewska, Ewelina; Dutsch-Wicherek, Magdalena (Contemporary Oncology/Współczesna Onkologia, 2018)
Breast cancer is the most frequently diagnosed type of cancer in women worldwide. Both the development and progression of breast cancer are related to tumour evasion of the immune system through a process called cancer immune-editing, in which regulatory lymphocytes play an important role. The infiltration of Treg cells in patients with breast cancer has been proposed as an independent unfavourable prognostic factor. In the present study, we aimed to evaluate the percentages of the Treg cell populations in the peripheral blood of patients with breast cancer with respect to progesterone receptor expression. Peripheral blood samples were collected from 27 patients with breast cancer treated in the Clinical Department of Breast Cancer and Reconstructive Surgery of the Professor Franciszek Lukaszczyk Oncological Centre, Bydgoszcz. Flow cytometry was used to evaluate the percentage of CD25+/FOXP3+/CD127 (–/low) T cells within CD3+/CD4+ T cells. The presence of CD25+/FOXP3+/CD127 (–/low) T cells within CD3+/CD4+ T cells was identified in all the examined blood samples. A statistically significantly higher percentage of CD25+/FOXP3+/CD127 (–/low) T cells within CD3+/CD4+ T cells was observed in progesterone receptor (PR)-negative breast cancer patients when compared to PR-positive breast cancer patients. The observed high percentage of CD25+/FOXP3+/CD127 (–/low) T cells within CD3+/CD4+ T cells in PR (–) breast cancer patients when compared to PR (+) breast cancer patients seems to confirm the unfavourable prognostic significance of these cells in breast cancer patients. This may indicate a rationale for combining standard oncological treatment in breast cancer patients with Treg-depleting therapy.